Sexual Transmission of Sars-Cov-2 Virus and Its Role in the Spread of Covid-19: A Living Systematic Review Protocol [Transmisión Sexual del Virus Sars-Cov-2 y Su Rol en la Propagación de Covid-19: Protocolo de Una Revisión Sistemática Viva] - Duarte-Anselmi, G (Medwave Estudios Ltda, 2020)
Objective To provide a review of the literature on the presence of SARS-CoV-2 in the sexual fluids of patients with COVID-19 and to observe its possible sexual transmission in a timely, rigorous, and continuously updated manner. Data sources We will conduct searches in PubMed/Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), grey literature, and a centralized repository in L·OVE (Living OVerview of Evidence). L·OVE is a platform that maps PICO questions to evidence from the Epistemonikos database. In response to the COVID-19 emergency, L·OVE was adapted to expand the range of evidence it covers and customized to group all COVID-19 evidence in one place. The search will cover the period until the day before submission to a journal. Eligibility criteria for selecting studies and methods We adapted an already published standard protocol for multiple parallel systematic reviews to the specificities of this question. We will include randomized trials evaluating the sexual transmission of the SARS-CoV-2 virus. Randomized trials evaluating the sexual transmission of other coronaviruses, such as MERS-CoV and SARS-CoV, and non-randomized studies in COVID-19 will be searched if no direct evidence from randomized trials is found or if the direct evidence provides a low to a very low level of certainty for critical outcomes. Two reviewers will independently screen each study for eligibility, extract data, and assess the risk of bias. We will perform random-effects meta-analyses and use GRADE to assess the certainty of the evidence for each outcome. A living, web-based version of this review will be openly available during the COVID-19 pandemic. We will resubmit the review if the conclusions change or if there are substantial updates. © 2020, Medwave Estudios Ltda. All rights reserved.